High-Sensitivity Cardiac Troponin T Improves the Diagnosis of Perioperative MI. (November 2017) - Brown, Jamie C.; Samaha, Eslam; Rao, Srikar; Helwani, Mohammad A.; Duma, Andreas; Brown, Frank; Gage, Brian F.; Miller, J. Philip; Jaffe, Allan S.; Apple, Fred S.; Scott, Mitchell G.; Nagele, Peter
Abstract : BACKGROUND: The diagnosis of myocardial infarction (MI) after noncardiac surgery has traditionally relied on using relatively insensitive contemporary cardiac troponin (cTn) assays. We hypothesized that using a recently introduced novel high-sensitivity cTnT (hscTnT) assay would increase the detection rate of perioperative MI. METHODS: In this ancillary study of the Vitamins in Nitrous Oxide trial, readjudicated incidence rates of myocardial injury (new isolated cTn elevation) and MI were compared when diagnosed by contemporary cTnI versus hscTnT. We probed various relative (eg, >50%) or absolute (eg, +5 ng/L) hscTnT change metrics. Inclusion criteria for this ancillary study were the presence of a baseline and at least 1 postoperative hscTnT value. RESULTS: Among 605 patients, 70 patients (12%) had electrocardiogram changes consistent with myocardial ischemia; 82 patients (14%) had myocardial injury diagnosed by contemporary cTnI, 31 (5.1%) of which had an adjudicated MI. After readjudication, 67 patients (11%) were diagnosed with MI when using hscTnT, a 2-fold increase. Incidence rates of postoperative myocardial injury ranged from 12% (n = 73) to 65% (n = 393) depending on the hscTnT metric used. Incidence rates of MI using various hscTnT change metrics and the presence of ischemic electrocardiogram changes, but without event adjudication, ranged from 3.6% (n = 22) to 12% (n = 74), a >3-fold difference. New postoperative hscTnT elevation, either by absolute or relative hscTnT change metric, was associated with an up to 5-fold increase in 6-month mortality. CONCLUSIONS: The use of hscTnT compared to contemporary cTnI increases the detection rate of perioperative MI by a factor of 2. Using different absolute or relative hscTnT change metrics may lead to under- or overdiagnosis of perioperative MI. Abstract : Published ahead of print July 14, 2017.